Penerapan Public Value Management Melalui Pembinaan Sosial: Studi Kasus di UPTD Pusat Pelayanan Sosial Griya Bina Karya - Muthmainnah, Sayyidah Afifah; Kartini, Dede Sri (Universitas Serang Raya, 2025)
Abstract This study aims to analyze the success of the Griya Bina Karya Regional Technical Implementation Unit (UPTD) in creating public value through a social development program for Social Welfare Service Recipients (PPKS). This study uses a descriptive qualitative approach with a case study method, data collected through observation, interviews and documentation. This study analyzes the effectiveness of the implementation of social development and its contribution to the creation of public value, especially in the dimensions of improving welfare, fulfilling basic rights, and strengthening social integration. The results of the study indicate that the Griya Bina Karya Social Service Center UPTD has succeeded in creating public value through the implementation of development based on work skills, basic education, and a religious approach. This success is supported by collaboration between stakeholders, siding with vulnerable groups, and the existence of periodic evaluations in program implementation. However, challenges such as limited resources and the sustainability of social reintegration are still obstacles that need to be addressed strategically. This study recommends strengthening institutional capacity and expanding partnership networks as strategic steps in strengthening the creation of sustainable public value. Keywords: Social Rehabilitation, Public Value Management, UPTD PPSGBK